2018
DOI: 10.15698/cst2018.05.134
|View full text |Cite
|
Sign up to set email alerts
|

Putting together and taking apart: assembly and disassembly of the Rad51 nucleoprotein filament in DNA repair and genome stability

Abstract: Homologous recombination is a key mechanism providing both genome stability and genetic diversity in all living organisms. Recombinases play a central role in this pathway: multiple protein subunits of Rad51 or its orthologues bind single-stranded DNA to form a nucleoprotein filament which is essential for initiating recombination events. Multiple factors are involved in the regulation of this step, both positively and negatively. In this review, we discuss Rad51 nucleoprotein assembly and disassembly, how it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 189 publications
(285 reference statements)
0
15
0
Order By: Relevance
“…RAD51 binding to ssDNA, and consequently the assembly and disassembly of the RAD51 filament, is dependent on RAD51 binding, the RAD51 protein levels and the activity of both positive and negative regulators of HR. Underscoring the importance of tightly controlling RAD51 activity, upregulation or downregulation is associated with genome instability and cancer ( 8 , 40 ).…”
Section: Rad51 and Genome Stabilitymentioning
confidence: 99%
“…RAD51 binding to ssDNA, and consequently the assembly and disassembly of the RAD51 filament, is dependent on RAD51 binding, the RAD51 protein levels and the activity of both positive and negative regulators of HR. Underscoring the importance of tightly controlling RAD51 activity, upregulation or downregulation is associated with genome instability and cancer ( 8 , 40 ).…”
Section: Rad51 and Genome Stabilitymentioning
confidence: 99%
“…Biochemical studies with eukaryotic proteins demonstrated that the ssDNA binding protein RPA, if added to the partially formed nucleoprotein filament, promotes the fully assembled Rad51 filament (reviewed in [56,69]). When added before Rad51, RPA binding affinity to ssDNA usually inhibits filament formation of Rad51 and Rad52 is required as a mediator on this RPA-coated ssDNA.…”
Section: Rada Catalyzes D-loop Formation On a Circular Dna Substratementioning
confidence: 99%
“…HR, which is generally considered to be an error-free process, may be an important source of genomic instability due to rearrangements between the invading and homologous strands with repetitive regions, formation of hairpins during D-loop extension, and difficulties associated with synthesis across repetitive regions, especially those that form DNA secondary structures [27,140–142]. The most important recombination proteins are Rad52 and Rad51 [96,98,143]. Deletion of RAD52 or RAD51 reduced the instability of repeat tracts compared to the psf1-1 mutant (Fig 5B–5D) what supports the conclusion that HR mechanisms are involved in this process (Fig 5F–5H).…”
Section: Discussionmentioning
confidence: 99%